FUNDAMENTAL POLITICO-LEGAL PRINCIPLES FOR SELF-DETERMINATION RIGHTS OF NATIONS AND NATIONALITIES - Tofiq, Nuriyeva Irada (International Journal of Research -GRANTHAALAYAH, 2018)
The article “Fundamental politico-legal principles for self-determination rights of nations and nationalities” provides description of principles for self-determination rights of nations and nationalities during different epochs. The principles for self-determination rights of nations and nationalities was formulated during the Age of Enlightenment and French Revolution as a theoretical weapon against Feudal State laws and against the Tsar regime and serfdom in Russia during the first quarter of XIX century. The Democratic movements in Russia, USA and European countries were mostly interested in overthrowing monarchies rather than in rights of nations. Soviet government required class and dialectic approach serving to the interest of Bolsheviks. When speaking about “rights of nations” or “rights of nationalities” W. Wilson intentionally forgot the “rights” of the native minor nations and nationalities and national minorities. So the issue of self-determination right for nations and nationalities remained unsettled. In early XX century Azerbaijan Democratic Republic and now Azerbaijan İndependent Republic provided the nations and nationalities living in the territory with the free space for development “regardless their sex, race, nationality, religious belief, social origin, political belief and other circumstances. In this case each nation, nationality and ethnic group must implement the level of their quality characteristics: steps and extent of development, number, occupied territory etc